2022
DOI: 10.3390/ma15155310
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Gamma-ray Shielding Performance of CuO-CdO-Bi2O3 Bentonite Ceramics

Abstract: The purpose of this research is to identify the radiation shielding capability of ceramics adding CuO, CdO, and Bi2O3 with diverse wt (%). The chemical compositions of the raw ceramics were documented through Energy Dispersive X-ray “EDX” techniques. For aesthetic appeal and solidification, CuO has been chosen to be added to ceramic. Moreover, in the interest of increasing the radiation shielding ability, the high atomic number and density of both CdO and Bi2O3 were suggested for the raw ceramics. To obtain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Before use, the residue was sifted and homogenized to ensure uniformity. WO 3 and Bi 2 O 3 NPs were prepared chemically by coprecipitation method [11,24] and used as fine aggregates added to the mortar composite to show the improvement of gamma-ray shielding properties, as with the addition of these particles, the density of the slurry composite increases. The ratio of the prepared mortar mixture to other studies aimed at improving the radiation shielding ability [25][26][27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before use, the residue was sifted and homogenized to ensure uniformity. WO 3 and Bi 2 O 3 NPs were prepared chemically by coprecipitation method [11,24] and used as fine aggregates added to the mortar composite to show the improvement of gamma-ray shielding properties, as with the addition of these particles, the density of the slurry composite increases. The ratio of the prepared mortar mixture to other studies aimed at improving the radiation shielding ability [25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…If heavy metal oxides (HMOs) are added, the density of the mortar will increase, enhancing the radiation absorption capability of the materials. Meanwhile, since these additives typically do not have a high neutron capture cross-section, their neutron shielding ability does not improve by the same amount, which is why it is useful to know the specifics of the application when designing the shielding material [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Sallem et al [13] demonstrated that ball-milled calcinated bentonite has a higher gamma-ray attenuation capacity than ordinary calcinated bentonite. Al-Ghamdi et al [14] deduced that pure bentonite ceramic, granite, and marble all exhibit less radiation shielding compared to bentonite ceramic with CdO and Bi 2 O 3 . The densities of barite and bismuth are equal to 4.5 g/cm 3 and 9.75 g/cm 3 , respectively, which are considered to be high densities.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation shielding study.-The prepared BiTeEu-glass samples were measured by experimental technique using a HPGe detector and three radioactive point sources covering low, medium and high energies. [30][31][32][33][34] The activity and their production time are tabulated in Table II. The geometry of experimental technique was presented in Fig.…”
mentioning
confidence: 99%